Associations of neighborhood walkability with intensity‐ and bout‐specific physical activity and sedentary behavior of older adults in Japan. Issue 9 (9th July 2019) - Amagasa, Shiho; Inoue, Shigeru; Fukushima, Noritoshi; Kikuchi, Hiroyuki; Nakaya, Tomoki; Hanibuchi, Tomoya; Sallis, James F; Owen, Neville
Abstract : Aim: We examined the relationships of objectively‐measured walkability with accelerometer‐measured activity patterns including bout‐specific moderate‐to‐vigorous physical activity (MVPA), light‐intensity physical activity (LPA) and sedentary behavior in older Japanese adults. Methods: This cross‐sectional study included 450 men and women (mean age 74 years) who were randomly selected from a resident registry of each municipality (Bunkyo, Fuchu and Oyama city). Neighborhood walkability was assessed using geographic information system data and activity patterns by a validated accelerometer (Active style Pro HJA‐350IT). MVPA was assessed as overall (all minutes), short‐bout (<10 min) and long‐bout (≥10 min). We used analysis of covariance to examine environmental relationships with the three MVPA measures, LPA and sedentary behavior by quartiles of walkability, adjusting for accelerometer wear time and sociodemographic, behavioral and health‐related factors. Results: In total, 27% of participants achieved ≥150 min/week of long‐bout MVPA. Walkability was not associated with overall MVPA (Q1 = 35.0, Q2 = 31.9, Q3 = 31.4, Q4 = 34.2 min/day) Older adults living in low‐walkability areas significantly accumulated more short‐bout MVPA (Q1 = 27.2, Q2 = 22.1, Q3 = 20.1, Q4 = 20.5 min/day) and LPA (Q1 = 346, Q2 = 311, Q3 = 289, Q4 = 284 min/day), but less sedentary behavior (Q1 = 479, Q2 = 520, Q3 = 544, Q4 = 544 min/day) than those living in high‐walkability areas. Conclusions: Those living in low‐walkability areas accumulated more LPA and short‐bout MVPA. These activities might be helpful targets for initiatives to promote physical activity among older adult residents of low‐walkability areas.Geriatr Gerontol Int 2019; 19: 861–867 .